Aquaporins in Pacific White Shrimp (Litopenaeus vannamei): Molecular Characterization, Expression Patterns, and Transcriptome Analysis in Response to Salinity Stress - Wang, Zhongkai; Chen, Yigeng; Wang, Cong; Zhao, Nannan; Zhang, Zhihao; Deng, Zhitong; Cui, Yanting; Wang, Renjie; Li, Yuquan (Frontiers in Marine Science, 2022)
Aquaporins (AQPs) are integral membrane proteins that facilitate the transport of water and small solutes across cell membranes. These proteins are vital for maintaining water homeostasis in living organisms. In mammals, thirteen aquaporins have been characterized, but in crustaceans, especially penaeid shrimp, the diversity, structure, and substrate specificity of these membrane channel proteins are largely unknown. We here presented the three types of AQPs from Litopenaeus vannamei based on genome and transcriptome sequencing. Phylogenetic analysis showed that each AQP separately represented members of aquaglyceroporins, classical aquaporins, and unorthodox aquaporins, thus they were named as LvAQP3, LvAQP4, and LvAQP11. The LvAqp4 was mostly expressed in hepatopancreas, stomach, and gill, meanwhile LvAqp3 and LvAqp11 were separately predominantly expressed in intestine and muscle, respectively. To investigate possible roles of aquaporins in osmoregulation, mRNA expression changes in mainly expressed tissues were analyzed after acute exposure or long-term acclimation to different salinities. The results revealed that the expression levels of aquaporins genes were significantly decreased in most tissues (except hepatopancreas) under salinity stress, though the expression patterns were variable among isoforms and tissues. Moreover, comparative transcriptome analysis indicated the combination roles of aquaglyceroporin and amino acid metabolism related genes and pathways in response to acute salinity changes in the intestine. This study opened new windows for future investigations and provided new insights into the role of aquaporins in osmoregulation in L. vannamei.